Why do community members believe mothers and babies are dying? Behavioral versus situational attribution in rural northern Ghana. (April 2020) - Aboungo, Victoria; Kaselitz, Elizabeth; Aborigo, Raymond; Williams, John; James, Kat; Moyer, Cheryl
Abstract: Objective: Rates of maternal and neonatal death remain high in the Global South, especially in Sub-Saharan Africa. In addition, indicators vary significantly by geography. This study aimed to understand what communities in northern Ghana with frequent maternal and newborn deaths or near deaths (near-misses) perceive to be the causes. As part of a larger study, four communities in Ghana's Northern Region were identified as areas with high concentrations of deaths and near-misses of mothers and babies. Design: Stakeholders were interviewed using in-depth interviews (IDIs) and focus-group discussions (FGDs). Field workers conducted 12 FGDs and 12 IDIs across a total of 126 participants. Setting: This exploratory descriptive study was conducted in the East Mamprusi District in the Northern Region of Ghana, in the communities of Jawani, Nagboo, Gbangu and Wundua. Participants: FGDs were led by trained field workers and attended by traditional chiefs and their elders, members of women's groups, and traditional birth attendants in each of the four study communities. IDIs, or one-on-one interviews, were conducted with traditional healers who manage maternal and neonatal cases, community health nurses, and midwives. Measurements and findings: Qualitative data were audio-recorded, transcribed, and thematically analyzed using the Attride-Sterling analytical framework. Discussions focused on where blame should be attributed for the negative outcomes of mothers and babies – with blame either being directed at the actions or inactions of the mothers (behavioral), or at the larger factors associated with poverty (situational) that necessitate mothers' behavior. For example, some respondents blamed women for their poor diets, while others blamed the lack of money or household support to buy nutritious foods. Blame was rarely attributed to the fathers despite local gender norms of males being the household decision-makers with regard to spending and care-seeking. Key conclusions: These findings contribute to a small but growing body of literature on the blaming of mothers for their own deaths and those of their newborns – a phenomenon also described in high-income countries – and is supported by blame attribution theories that explain the self-protective nature of victim-blaming. Implications for practice: These results carry important implications for education and intervention design related to maternal and neonatal mortality, including more focused efforts at incorporating men and the larger community. More research is warranted on blame attribution for these adverse outcomes and its effects on the victims.